Corporate Social Responsibility Practices and Economic Performance in Colombia: The Moderating Effect of Family Control - Alzate-Gómez, Juan Diego; Cortés, Diógenes Lagos; Fieldman, Percy Marquina (International Journal of Economics and Financial Issues, 2019)
The purpose of this descriptive-quantitative study was twofold. On the one hand, it seeks to determine the relationship between the implementation of CSR practices and economic performance. On the other, it seeks to identify the effect of family control on the CSR-Performance relationship. For this, we studied a sample of 55 companies listed on the stock exchange of Colombia during the period 2010-2017. The analysis was performed with multiple regression models estimated from the GMM method. Three findings are highlighted: (a) No evidence was found about a relationship between the family character and the adoption of CSR practices; (b) Evidence was found on a direct relationship between the adoption of CSR practices and economic performance; and (c) the family character does not influence the CSR-Performance relationship. Keywords: Family business, Corporate Social Responsibility, Economic Performance JEL Classifications: G30, G34, L25 DOI: https://doi.org/10.32479/ijefi.8856